Civic Engagement: Connecting Adolescents' Voice through Social Media and the Implications for Government Policy-Making - Kusumasari, Bevaola (Kusumasari,Bevaola, 2013)
Citizen participation, in simple terms, is understood to mean taking part in the government decision-making process. The development of social networking seems to afford a new way for the youth to engage in government decision and policy making. This study aims to determine whether social media is an effective policy-making tool and means of community political participation by examining the way teenagers use social media to participate in politics. The study involves a survey of 120 teenagers drawn from the 13-19 year-old age group in Yogyakarta, Indonesia, and the observation of the teenagers'status inputs on Facebook and Twitter The findings show that there has been a shift in the way teenagers participate in communication. It is evident that social networking has the potential of becoming a major means of teenager participation in politics owing to its practicality, flexibility and ability to enable them to express their political and social concerns in personal ways. The findings also highlight the importance of social networking as space which the government can use to engage teenagers' voice in policy formulation. This article ends by describing the contextual issues teenagers encounter in their lives, and reviews the literature on adolescents' participation in politics.